Soil fungal and bacterial communities reflect differently tundra vegetation state transitions and soil physico-chemical properties ... - Huusko, Karoliina; Manninen, Outi H.; Myrsky, Eero; Stark, Sari (Mendeley Data, 2024)
Supplementary data for the manuscript entitled "Soil fungal and bacterial communities reflect differently tundra vegetation state transitions and soil physico-chemical properties", New Phytologist. The excel file contains information of the experimental design, plant, fungal and bacterial communities, soil physico-chemical properties and site associated data. There are 8 sheets in total in the file: the first sheet contains descriptions for data sheets and variables, and other sheets actual data. Sheets: *Description_of_data: Description of data sheets and variables *Experimental_design: Information of the experimental design. *Soil_variables: Site related information of soil physico-chemical variables, extracellular enzyme activities, microbial respiration *Plant_community: Plant community data *ITS2_OTU_table_L7: Fungal species level operational taxonomic units (OTUs) and their sequence counts *ITS2_OTU_taxonomy_functional: Taxonomic and functional information related fungal OTUs *16S_OTU_table_L7: 16S ...